Estimated US manufacturing production capital and technology based on an estimated dynamic economic model - Baoline Chen; Peter A. Zadrozny (Center for Economic Studies and ifo Institute (CESifo), 2005)
Production capital and technology, fundamental to understanding output and productivity growth, are unobserved except at disaggregated levels and must be estimated prior to being used in empirical analysis. We develop and apply a new estimation method, based on advances in economics, statistics, and applied mathematics, which involves estimating a structural dynamic economic model of a representative production firm and using the estimated model to compute Kalman-filtered estimates of capital and technology for the sample period. We apply the method to annual data from 1947-97 for U.S. total manufacturing and compare the estimates with those reported by the Bureau of Labor Statistics.
Keywords: C50; L60; D24; C81; 330; Kalman filter estimation of unobserved state variables; Gesamtwirtschaftliches Anlagevermögen; Technologie; Verarbeitendes Gewerbe; Schätztheorie; Zustandsraummodell; Schätzung; Theorie; USA